Research challenges of autonomic computing - Kephart, Jeffrey O. (Proceedings of the 27th international conference on Software engineering, 2005)
Autonomic computing is a grand-challenge vision of the future in which computing systems will manage themselves in accordance with high-level objectives specified by humans. The IT industry recognizes that meeting this challenge is imperative; otherwise, IT systems will soon become virtually impossible to administer. But meeting this challenge is also extremely difficult, and will require a worldwide collaboration among the best minds of academia and industry. In the hope of motivating researchers in relevant areas to apply their expertise to this vitally important problem, I outline some of the main scientific and engineering challenges that collectively make up the grand challenge of autonomic computing, and provide pointers to initial efforts to address these challenges.